A principal component analysis of polycyclic aromatic hydrocarbon emission in NGC 2023. Issue 1 (14th October 2020) - Sidhu, Ameek; Peeters, Els; Cami, Jan; Knight, Collin
ABSTRACT: We use the measured fluxes of polycyclic aromatic hydrocarbon (PAH) emission features at 6.2, 7.7, 8.6, 11.0, and 11.2 μ m in the reflection nebula NGC 2023 to carry out a principal component analysis (PCA) as a means to study previously reported variations in the PAH emission. We find that almost all of the variations (99 per cent) can be explained with just two parameters – the first two principal components (PCs). We explore the characteristics of these PCs and show that the first PC ( PC 1 ), which is the primary driver of the variation, represents the amount of emission of a mixture of PAHs with ionized species dominating over neutral species. The second PC ( PC 2 ) traces variations in the ionization state of the PAHs across the nebula. Correlations of the PCs with various PAH ratios show that the 6.2 and 7.7 μ m bands behave differently than the 8.6 and 11.0 μ m bands, thereby forming two distinct groups of ionized bands. We compare the spatial distribution of the PCs to the physical conditions, in particular to the strength of the radiation field, G 0, and the G 0 / n H ratio and find that the variations in PC 2, i.e. the ionization state of PAHs are strongly affected by G 0 whereas the amount of PAH emission (as traced by PC 1 ) does not depend on G 0 .